Analisis Determinan Tingkat Pengangguran Terbuka di Pulau Jawa: Tinjauan dari Sisi Perekonomian dan SDM - Desi Dwi Liana; Nurjannah Rahayu Kistanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this research is to analyze the effects of economic growth, micro and small industries human development index, and populations on the open unemployment rate in Java Island over the period 2015 to 2024. This study employs a quantitative approach using panel data regression analysis with the Fixed Effect Model (FEM) as the selected estimation method. The data were sourced from Central Statistic Agency (BPS). The results indicate a simultaneous effect of all four independent variables on the dependent variable. The panel data estimation findings reveal that economic growth and the human development index have a significant negative effect on the open unemployment rate in Java Island. Meanwhile, populations demonstrate a significant positive effect on the open unemployment rate. In contrast, the micro and small industries variable shows no significant effect on the open unemployment rate in Java Island. This study contributes to the advancement of labor economics literature, particularly in understanding the dynamics of open unemployment at the regional level, and provides practical recommendations for regional governments in formulating more effective and targeted employment policies.